Wave-particle interactions toolset: A python-based toolset to model wave-particle interactions in the magnetosphere - Tourgaidis, Stelios; Sarris, Theodore (Frontiers in Astronomy and Space Sciences, 2022)
Wave particle interactions are known to be an efficient yet unquantified driver of the variability of particle populations in Earth’s magnetosphere, and their quantification and understanding through modelling has been a subject of extensive research during the last decades. Moreover, there is an increasing interest in techniques for radiation belt remediation, which refers to artificially controlling energetic particle populations in the near-Earth space environment via the scattering of particles from artificially generated electromagnetic waves. Whereas numerous modelling techniques are described in literature, there is a lack of a unified open-source toolset that incorporates the equations and parameterizations used by different wave-particle interaction models in a user-friendly environment. We present WPIT, the Wave-Particle Interactions Toolset, an open source, Python-based set of tools for modelling the interactions between energetic charged particles and VLF waves in the magnetosphere through test particle simulations. WPIT incorporates key routines related to wave-particle interactions in Python modules and also in Jupyter Notebook environment, enabling the traceability of all relevant equations in terms of their derivation and key assumptions, together with the programming environment and integrated graphics that enable users to conduct state-of-the-art wave-particle interaction simulations rapidly and efficiently. WPIT can be used either as a stand-alone simulation tool or as a library of routines that the user can extract and incorporate into an independent simulation. We present an analytic description of the code, the methodology used, and examples based on each of the WPIT modules. WPIT examples include the exact reproduction of simulation results that have been reported in literature, based on the same sets of parameters and assumptions, allowing the user to expand upon state-of-the-art. Finally, using the WPIT toolset, we perform a parametric analysis on the onset of nonlinear interactions between electrons with whistler-mode waves by varying the relevant parameters of the waves (amplitude, wave normal angle and frequency), the particles (pitch angle and energy) and the plasma environment (electron density and ion composition).